BRACU new campus development project construction schedule (1.05.22-30.05.22) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the submission of construction schedule from 1 May, 2022 to 31 May, 2022 of BRACU new campus project.